Eksistensi dan Resistensi Tradisi Mendoangan di Desa Parangian Kecamatan Baraka Kabupaten Enrekang - Sumarni Kasmir (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This study aims to determine the mandoangan process in the village of Warian, the values ​​contained in the mandoangan tradition and the existence of a tradition of 40 days of death (mandoangan) in the village of Perangian, Baraka District, Enrekang Regency. This study uses a qualitative approach. Data is collected through interviews, direct observation and documentation. The data obtained is organized into categories and collected into units and choosing which ones are important and conclusions are made. The results showed that: (1) the mandoangan tradition was carried out when there were dead people to pray for the deceased, massubak litak, mangbala batu, bongi horn, karuen bala batu, mandoangan, and also providing siri leaves, lime, areca nut, banana leaves, water white, incense, sugar cane, and barasanji which have been inherited from generation to generation in the Peragian Village community; (2) The values ​​contained in the madoangan tradition in particular such as spiritual and religious values, while the general values ​​such as the value of solidarity or the value of mutual cooperation; (3) The existence of a tradition of 40 days of death (madoangan) is attributed to the existence of a consistent attitude in the Warian village community. In addition, hereditary cultural inheritance is one aspect that has kept this tradition until now.